KONSEP PENGELOLAAN WAKAF OLEH NAZHIR UNTUK USAHA PRODUKTIF DEMI TERWUJUDNYA KESEJAHTERAAN SOSIAL DI INDONESIA - Yasniwati Yasniwati (UNES Law Review, 2023)
Waqf is a worship that is highly recommended by Rasulullah SAW. Waqf a practice that will always flow through his thighs even though he has passed away. In addition to the waqf, there was a manager who was asked by the waqif to manage the waqf assets that he gave, namely Nazhir. Nazhir existence in the development of waqf is very important, this can be likened to a manager in a company. He plays the role of developing waqf to produce something that is useful for religious and social interests in accordance with the hopes and intentions of the endowment. As a manager, Nazir can be formed from one or several people or institutions and also a Legal Entity. Waqf management should be able to manage waqf assets and the benefits of managing waqf are utilized for the welfare of the people.